Influence of Highly Charged Ion Irradiation on the Electrical and Memory Properties of Black Phosphorus Field‐Effect Transistors - Stephan Sleziona; Osamah Kharsah; Lucia Skopinski; Leon Daniel; Jennifer Schmeink; Marika Schleberger (Advanced Electronic Materials)
Abstract Black phosphorus (bP) is one of the more recently discovered layered materials. Utilizing the hysteresis in the transfer characteristics of bP field‐effect transistors (FETs), several approaches to realize non‐volatile memory devices are successfully demonstrated. This hysteresis is commonly attributed to charge trapping and detrapping in impurities and defects whose nature and location in the device are however unclear. In this work, defects are deliberately introduced into bP FETs by irradiating the devices with highly charged Xe30 + at a kinetic energy of 180 and 20 keV to manipulate their electrical and memory properties. The results show for the ion with higher energy an increase of conductance and an increase of p‐doping of up to 1.2 · 1012 cm−2 with increasing fluence, while the charge carrier mobility degrades for the higher ion fluences. Most notably, an increase in the hysteresis' width and of the memory window are observed due to the irradiation. By controlling the kinetic energy of the ions, it can be demonstrated, that the modifications of electronic properties arise from defects in bP and the underlying SiO2 substrate. However, changes in hysteretic properties are attributed exclusively to irradiation‐induced defects in the substrate, so ion irradiation can significantly improve the properties of bP based memory devices.